Simultaneous Enhancement of Thermostability and Catalytic Activity of Phospholipase A(1) by Evolutionary Molecular Engineering - Song, Jae Kwang (American Society for Microbiology, 2000)
The thermal stability and catalytic activity of phospholipase A(1) from Serratia sp. strain MK1 were improved by evolutionary molecular engineering. Two thermostable mutants were isolated after sequential rounds of error-prone PCR performed to introduce random mutations and filter-based screening of the resultant mutant library; we determined that these mutants had six (mutant TA3) and seven (mutant TA13) amino acid substitutions. Different types of substitutions were found in the two mutants, and these substitutions resulted in an increase in nonploar residues (mutant TA3) or in differences between side chains for polar or charged residues (mutant TA13). The wild-type and mutant enzymes were purified, and the effect of temperature on the stability and catalytic activity of the enzymes was investigated. The melting temperatures of the TA3 and TA13 enzymes were increased by 7 and 11°C, respectively, compared with the melting temperature of the wild-type enzyme. Thus, we found that evolutionary molecular engineering was an effective and efficient approach for increasing thermostability without compromising enzyme activity.